Fragment-based drug discovery for disorders of the central nervous system: designing better drugs piece by piece - Chan, Bill W. G. L.; Lynch, Nicholas B.; Tran, Wendy; Joyce, Jack M.; Savage, G. Paul; Meutermans, Wim; Montgomery, Andrew P.; Kassiou, Michael (Frontiers in Chemistry, 2024)
Fragment-based drug discovery (FBDD) has emerged as a powerful strategy to confront the challenges faced by conventional drug development approaches, particularly in the context of central nervous system (CNS) disorders. FBDD involves the screening of libraries comprising thousands of small molecular fragments, each no greater than 300 Da in size. Unlike the generally larger molecules from high-throughput screening that limit customisation, fragments offer a more strategic starting point. These fragments are inherently compact, providing a strong foundation with good binding affinity for the development of drug candidates. The minimal elaboration required to transition the hit into a drug-like molecule is not only accelerated, but it allows for precise modifications to enhance both their activity and pharmacokinetic properties. This shift towards a fragment-centric approach has seen commercial success and holds considerable promise in continuing to streamline the drug discovery and development process. In this review, we highlight how FBDD can be integrated into the CNS drug discovery process to enhance the exploration of a target. Furthermore, we provide recent examples where FBDD has been an integral component in CNS drug discovery programs, enabling improvements of pharmacokinetic properties that have previously proven challenging. The FBDD optimisation process provides a systematic approach to explore the vast chemical space, facilitating the discovery and design of compounds piece by piece, capable, of modulating crucial CNS targets.